How Does the Show and Tell Method Enhance Public Speaking Skills? A Case Study of Third-Grade Students at Muhammadiyah Noyokerten Elementary School - Handung Jaya , Patria; Afif Nabila , Roihana (Mutiara Intelektual Indonesia Press, 2025)
This qualitative case study investigates the impact of the Show and Tell method on the public speaking skills development of third-grade students at SD Muhammadiyah Noyokerten, Sleman, Yogyakarta, conducted from April to May 2025. Participants included the school principal, two third-grade teachers (Classes III A and B), and 48 students. Data collection involved systematic observations, semi-structured interviews, and documentation analysis, with triangulation ensuring data validity. The analysis followed Miles and Huberman’s interactive model. Results indicated that Show and Tell significantly improved students’ public speaking competencies. Quantitative results showed increased student confidence (from 45% to 78%), enhanced vocabulary (15-20 new words per student per month), and improved fluency (mean speaking assessment scores rose from 62.3 to 81.7 over two semesters). Qualitative findings highlighted the importance of interactive teaching methods, supportive teacher facilitation, and a positive peer environment in skill development. However, challenges such as initial self-confidence issues (62% of students), limited vocabulary (58%), fear of errors (54%), and limited practice time due to scheduling constraints persisted. Positive supporting factors included teacher encouragement, scaffolding, parental involvement, and a psychologically safe classroom environment. In conclusion, the Show and Tell method is effective in fostering public speaking skills in elementary students when combined with appropriate teaching strategies and a conducive learning environment. Success is dependent on addressing individual barriers, offering ample practice opportunities, and ensuring collaboration between teachers, parents, and school administrators